2010
DOI: 10.1038/ajg.2010.47
|View full text |Cite
|
Sign up to set email alerts
|

Is Irritable Bowel Syndrome a Diagnosis of Exclusion? A Survey of Primary Care Providers, Gastroenterologists, and IBS Experts

Abstract: OBJECTIVES-Guidelines emphasize that irritable bowel syndrome (IBS) is not a diagnosis of exclusion and encourage clinicians to make a positive diagnosis using the Rome criteria alone. Yet many clinicians are concerned about overlooking alternative diagnoses. We measured beliefs about whether IBS is a diagnosis of exclusion, and measured testing proclivity between IBS experts and community providers.METHODS-We developed a survey to measure decision-making in two standardized patients with Rome III-positive IBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(163 citation statements)
references
References 23 publications
5
151
0
7
Order By: Relevance
“…As a result, non-experts demonstrated an increased utilization of resources, particularly in those presenting with D-IBS. 28 This highlights that, despite decades of expert opinion, clinicians remain concerned about the possibility of a missed organic pathology in patients meeting criteria for IBS. This is reinforced by the fact that celiac disease may account for up to 4% of IBS cases, 7 which subsequently led to a paradigm shift in international guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, non-experts demonstrated an increased utilization of resources, particularly in those presenting with D-IBS. 28 This highlights that, despite decades of expert opinion, clinicians remain concerned about the possibility of a missed organic pathology in patients meeting criteria for IBS. This is reinforced by the fact that celiac disease may account for up to 4% of IBS cases, 7 which subsequently led to a paradigm shift in international guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Such uncertainties are already apparent in clinical practice where healthcare professionals vary greatly in their beliefs as to whether IBS is a diagnosis of exclusion. 28 A survey conducted in the USA amongst primary care physicians, community -IB" internationally recognized panel of IBS key opinion leaders, revealed that non-experts were far more likely to endorse IBS as a diagnosis of exclusion (72% vs. 8%). As a result, non-experts demonstrated an increased utilization of resources, particularly in those presenting with D-IBS.…”
Section: Discussionmentioning
confidence: 99%
“…Most investigators have used a normal colonoscopy as confirmation of a diagnosis of IBS; 12 that is, physicians still regard IBS as a diagnosis of exclusion, which is perhaps justified by the modest performance of the different symptom-based criteria for IBS proposed over the last four decades. 11,13 Indeed, the current level of diagnostic confidence, based exclusively on these criteria, has not reduced the performance of testing such as colonoscopy and biopsies in some settings, 14 despite the desirability to enhance high-value care.…”
Section: Irritable Bowel Syndrome (Ibs) Is a Chronic Functional Gastrmentioning
confidence: 99%
“…The direct and indirect costs of IBS in the US exceed $30 billion per year and the condition is associated with approximately 3.6 million annual physician visits (9,10). The diagnosis of IBS, particularly in primary care, is widely viewed as a diagnosis of exclusion established by negative testing for organic gastrointestinal or systemic diseases, consequently leading to dramatically higher health care costs related to diagnostic testing (11,12).…”
Section: Introductionmentioning
confidence: 99%